THE IMPORTANCE OF SPEAKING ACTIVITIES IN TEACHING ENGLISH - Rustamova, Shokhista Sharifovna (INTERNATIONAL CONFERENCES, 2023)
Speaking is defined as an effective means for those students who learn a foreign language as a second for end of communication with other individuals or on the other hand speaking is a way of successfulness for learner of foreign language so as to make an easy communication with others. Meanwhile, speaking is an underdeveloped skill which is gained by foreign language learners through practice opportunities provided them in learning classes for using of his ears and eyes instead of their mouths. Speaking is a qualification of a learner of language learning class for end of communication with others in the daily lives.